Geschichte der italienischen Literatur in Österreich Teil 1: Von den Anfängen bis 1797 - Noe, Alfred (2011)
Towards the end of the 20th century the Italian literature created outside Italy finally started to receive proper attention, because research began to focus on the socio-cultural analysis of the different forms of internal and external postcolonialism. As a result, both imperialism and nationalism are seen as responsible for phenomena of cultural alienation in many territories outside as well as inside the national borders of the country and are exposed as ideological constructs. Nevertheless research still neglects the one undoubtedly outstanding region in the production of Italian literature outside Italy, i.e. Austria, more precisely the territories of the Habsburg Monarchy, where for nearly 500 years - from early Humanism to the First World War - the tradition was the richest in quantity as well as in quality. This first part of a comprehensive history of the Italian literature created in Austria for an Austrian public has been written with the intention of filling this gap. The unique position the Italian language held at Vienna's imperial court at least from the middle of the 17th to the middle of the 18th century is well known: Italian was not only an official language for the purpose of representation, it also served as a vehicle of cultural communication in the inner circle of the imperial family. The numerous political connections between the House of Habsburg and the ruling Italian dynasties are a major reason for the manifold cultural transfers between the Austrian territories and the Italian States. The great number of strategic marriages led to intense cultural as well as economical relations, which obviously did result in occasional implications in territorial conflicts and in military alliances not always favorable to the mutual understanding. As a consequence of the above mentioned economical and dynastical connections the Habsburgs often intervened politically in Italy, first in the Early Modern Period, especially during the reigns of Charles V and Ferdinand I. Two centuries later, the Habsburg administration of the Kingdom of Naples (1707-1734) as well as of Lombardy during most of the 18th century (1714-1797) was decisive for the continuation of those interchanges, which ended however, when the Italian movement of unification began to create a totally new situation. Humanism, baroque and enlightenment, three currents which are amply discussed in the present volume, could more easily expand from Italy to Austria because of the before described dynastical connections and they established themselves still deeper because of the immigration or the long stays of Italian authors in the cultural centers of the Austrian monarchy, first of all of course in Vienna. Not surprisingly however, we possess so far only an inadequate and unsystematic documentation of the activities and literary productions of the great majority of those authors: As is well known, the 19th century created a nationalistic base for literary studies, a view which still for a long time influenced the 20th century for a long time. The Italian authors working and publishing in Austria did so in their own language, but in a foreign country and for a foreign sovereign. For this reason they obtained practically no attention in Austrian literary studies, because there works were not composed in the national language, and their appearance in Italian studies is all but nonexistent because they made no direct contribution to the national literary tradition.